Morphological and anatomical variations among varieties of Ficus Deltoidea Jack (mas cotek) from the East Coast of Peninsular Malaysia - Nor Zaimah Ab. Rashid
Ficus deltoidea Jack (F.deltoidea) commanly knows as Mas Cotek is a member of the Moraceae family. Six varieties named as F. deltoidea Jack. var, deltoidea Corner, F.deltoidea Jack var. bilobata Corner, F.deltoidea Jack var. angustifolia (Miq.) Corner, F.deltoidea Jack var. kunstleri (King) Corner, F.deltoidea Jack var. intermedia Corner and F.deltoidea Jack var. trengganuensis Corner from the East Coast of Peninsular Malaysia. and kept as living collection in the Faculty of Agriculture, Biotechnology and Food Science (FPBSM) Nurseries, were used in this study. The taxonomic classification of F.deltoidea has been recognized based on the morphological characteristics of the leaf, fig (syconium) and growth habit. Quantitative and qualitative morphological and anatomical data were measured in all varieties studied. The quantitative morphological parameters of leaf and syconium were found to be significantly different between varieties. For anatomical studies, there were several significant differences among the F.deltoidea varieties especially the petiole character, while for leaf midrib and lamina, there were variations in the outer shape and layers of epidermal cells. A total of 245 germplasm (accessions) were collected from field trip in Peninsular Malaysia and planted in the FPBSM Nursery as the Living Collection, and 252 herbarium specimens from three herbaria, were observed and recorded for ecological conspectus study. The distribution data were used to plot a map by using DIVA-GIS software. The morphological and anatomical characteristics as well as the ecological conspectus for six varieties have been analyzed and reported in this research to support the taxonomy of F.deltoidea varieties from the East Coast of Peninsular Malaysia phytogeographical region.